(untitled) (Journal of the Management Sciences, 2026)
This study provides an explanatory framework from socio-economic development theory for MSME growth in Lagos State, focusing on both formal and informal institutional factors. The study is grounded in North’s Institutional Theory, which posits that the development of formal and informal institutions is crucial for socio-economic progress, with consequent effects on MSME development. The conceptual review examines MSMEs and their role in socio-economic development. It discusses various definitions and classifications of MSMEs, as well as the key institutional factors influencing their growth. A desk review approach was employed, involving an extensive review of academic literature, reports, and other credible sources. The study concludes that both formal and informal institutions significantly impact the development and sustainability of MSMEs in Lagos. A favourable socio-economic environment, driven by the positive interplay among these institutions, is essential for MSME growth and contributes to broader economic and social development. It therefore recommends that policymakers strengthen both formal and informal institutions to create a supportive environment for MSMEs. This includes improving legal and regulatory frameworks, addressing financial challenges, and fostering a collaborative socio-economic climate.